Efficacy of a mandibular advancement intraoral appliance (MOA) for the treatment of obstructive sleep apnea syndrome (OSAS) in pediatric patients: A pilot-study - Modesti-Vedolin, Gabriela; Chies, Caroline; Chaves-Fagondes, Simone; Piza-Pelizzer, Eduardo [UNESP]; Lima-Grossi, Márcio (Medicina Oral, S.L., 2018)
Background: To evaluate the treatment efficacy of a mandibular advancement intraoral appliance (MOA) for treatment of obstructive sleep apnea syndrome (OSAS) in pediatric patients. Material and Methods: Eighteen patients (mean=8.39 years old, women=44.4%) were selected. Sleep disorders, sleep bruxism, and temporomandibular disorders were assessed by the Sleep Disturbance Scale for Children (SDSC), the BiteStrip® (portable SB device), and the Research Diagnostic Criteria for Temporomandibular Disorders, respectively. The clinical diagnosis of OSAS was confirmed with a type 3 portable monitor device (Apnea Link TM Plus). A silicon-based material MOA was used by patients for 60 days, and the results were compared to baseline. Results: The median RDI was significantly reduced from 10 to 4.5 events/hour. Nadir SpO2 significantly increased from 82.6% to 88.9%. Total snoring events/hour have also significantly decreased from 205.5 to 91.5. Signs and symptoms of TMD remained unaltered. There was also a reduction from moderate to absence of SB in 12 patients. Similarly, all variables measured by the SDSC have had very significant reductions: disorders of initiating and maintaining sleep, sleep disordered breathing, disorders of arousal, nightmares, sleep wake transition disorders, disorders of excessive somnolence, and sleep hyperhidrosis. Conclusions: In selected cases, OA maybe considered as an alternative for the OSAS treatment.
Keywords: Bruxism; Children; Sleep apnea; Sleep disorders; Snoring appliances